Quantification of agricultural and forestry waste biomass to production of compacts for power generation (Revista de Ciências Agroveterinárias, 2017)
The objective of this study was to quantify and locate regionally in the State of Santa Catarina the agricultural and forestry waste biomass with potential for densification for energy production. The study involved data from annual agricultural and forestry production from the year 2012. A value called technical coefficient, found in the literature, was used to determine the amount of agricultural (from temporary and perennial crops) and forest residues generated for each culture. Two standards were used for the discussion of the data: the amount of waste generated and the geographical location. The maize crop generated the biggest amount of waste in 2012, followed by forestry, upland rice and soybeans. The Southern, the Western and the Mountains are the mesoregions that produced the most waste in 2012. Residues from forestry, maize, rice and soybeans are those with the greatest potential in terms of quantity and geographical location for densification for energy production.
Keywords: biomass energy; crop residues; energy potential.